Quantification of small cell numbers with a microchannel device. (September 2008) - Badders, Nisha M.; Yu, Hongmei; Alexander, Caroline M.; Beebe, David J.
The ability to precisely quantify rare populations of cells has become an essential first step of many cell-based assays in stem cell research. Since current devices for cell quantification require relatively high cell concentrations and/or absolute cell numbers, we have developed a microchannel-based device, allowing precise quantification of limiting cell numbers/concentrations. We anticipate this device will serve as an important tool to overcome a practical obstacle in stem cell research.